Logistics and Production Management - Martins, A.; Camelo, A. (2011)
Logistics and Operations are well known for providing and sustaining some of the company’s competitive advantages. This is the baseline approach developed of this book. We analyse the overall perspective on the supply area and the internal company were procurement and sourcing are approached to secure the best suppliers, and enhance a competitive position in the market. Also, it is presented an approach to the internal flows and the operations planning, so that managers may reduce the need for working capital and increase value for the customers. We take a look at facilities and their internal organization. Firstly, location models are analysed so that the transportation distance may be minimised. Then the internal facility is considered in terms of its flows, the products and the aims for different types of facilities. Lastly, we analyse transportation. The aim of this last chapter is to give an approach to their present situation and be able to choose the best alternative to supply value to their customers while reducing costs and preventing major investments at an initial phase, but also to establish guidelines for future decisions in the case of expansion. The balance between minimizing costs and providing the best possible experience (in order to retain customers and secure the company) is the last point of discussion.